“Esa historia no puede contarse”. La dificultad de representar el pasado en dos novelas de Javier Cercas - Magda, Potok (Wydawnictwo Naukowe UAM, 2013)
In two novels based on the subject of war: Soldados de Salamina (“Soldiers of Salamis”) (2001) and Velocidad de la luz (“the Speed of Light”) (2005), Javier Cercas raises the problem of recuperation of a traumatic past through literary discourse. The questions which these novels discuss and which we want to examine here concern complex relations between fiction and reality, history and memory (individual and collective), guilt and responsibility. In order to confront the historical reality from the contemporary perspective, from postmemory, Javier Cercas proposes a narrative with a clear metafictional dimension creating interferences in distinct narrative levels.
“This story is impossible to be told”. Difficulty in depicting the past in two novels by Javier Cercas
Keywords: contemporary Spanish fiction; Javier Cercas; postmemory; historiographic metafiction